Alemtuzumab Improves Cognitive Processing Speed in Active Multiple Sclerosis—A Longitudinal Observational Study - Riepl, Ester; Pfeuffer, Steffen; Ruck, Tobias; Lohmann, Hubertus; Wiendl, Heinz; Meuth, Sven G.; Johnen, Andreas (Frontiers in Neurology, 2018)
Background: Several disease modifying drugs (DMDs) have shown promising effects on cognitive impairment in multiple sclerosis (MS). Alemtuzumab, a humanized monoclonal antibody, is effective in controlling disease activity, however has not been evaluated for its effects on cognition in detail so far. Objective: To explore the influence of alemtuzumab on cognitive impairment in active relapsing-remitting MS (RRMS) as well as possible clinical and neuroimaging predictors of cognitive changes during the first year of therapy. Methods: Extensive neuropsychological assessment was administered to 21 patients with active RRMS at baseline and again after the second treatment with alemtuzumab (mean time span: 15.05 months). Clinical and routine structural neuroimaging markers were explored for their capacity to predict individual courses of cognitive change. Results: Overall cognitive functioning remained stable or improved during the observational period of alemtuzumab treatment on average. Scores on two neuropsychological tests of processing speed significantly improved and clinically relevant individual gains of processing speed were seen in the majority of patients. Linear regression models showed that clinical and routine neuromimaging measures of disease activity could not fully account for these cognitive changes. Conclusions: Results suggest that alemtuzumab treatment in active RRMS stabilizes overall cognitive functioning and furthermore positively affects cognitive processing speed. Changes in processing speed were independent from clinical and structural neuroimaging parameters of disease activity and may thus represent an underrated and independent outcome measure to evaluate treatment effects.